Case report: An incidental finding of a left-sided supernumerary kidney - Getachew, Aklilu; Suga, Nathan K.; Suga, Jochebed K.; Kiflemariam, Nuhamin D. (Frontiers in Medicine, 2025)
A supernumerary kidney is an extremely rare congenital renal anomaly that is characterized by the presence of one or more extra kidneys. Unilateral cases occur more commonly on the left side. Reporting such uncommon anomalies is important for several reasons, such as improving diagnosis and treatment, educating clinicians and radiologists about the identification and treatment of supernumerary kidneys, and comparing the case to existing literature to highlight similarities and differences in presentation, management, or outcomes. A 35-year-old male patient presented to our hospital in Addis Ababa, Ethiopia, with left lower flank pain. His blood pressure was elevated during the initial visit; however, the results of the physical examination and laboratory investigations were unremarkable. Abdominopelvic ultrasound and computed tomographic (CT) urography confirmed the diagnosis of a left-sided supernumerary kidney, with no associated abnormalities. In such cases, the diagnosis of a supernumerary kidney is made using an abdominal ultrasound scan, intravenous urography (IVU), CT urography, and magnetic resonance imaging (MRI). Treatment depends on the patient’s symptoms. Asymptomatic cases must be followed up regularly. If a supernumerary kidney is nonfunctional or associated with other abnormalities, a nephrectomy is indicated. We treated our patient with adequate analgesia and scheduled a follow-up.